The fast converging method of calculation of wire radiators in infinite planar phased antenna array - Kudzin, V. P. (Видавництво Національного університету "Львівська політехніка", 2009)
The effective fast converging method of calculation of wire radiators in infinite planar phased antenna array is developed. The method is based on use of Green’s function submitted as double series with accelerated convergence. The moment method is applied and piecewise sine basic and weight functions automatically satisfied to Kirchhoff’s current law are used. Expressions for impedance matrix elements consist of two series. Members of the series generated by spectral part of Green’s function are represented as the closed analytical expressions. Members of series generated by spatial part of Green’s function are calculated numerically by one-fold integration.
Keywords: Infinite phased array; numerical methods; integral equations; thin wire radiator; Green’s function